Reduction of BOD, COD, and TSS in Textile Wastewater Using Bentonite Activated Charcoal Adsorbent - Aritonang, Barita; Ritonga, Ahmad Hafizullah; Harefa, Karnirius; H, Herlina (Jurnal FARMASIMED (JFM), 2025)
Wastewater generated by the textile industry contains a variety of hazardous contaminants, including complex organic compounds, synthetic dyes, surfactants, heavy metals, and critical pollution indicators such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), and total suspended solids (TSS). This study evaluates the efficacy of a dual-adsorbent system comprising hydrochloric acid-activated bentonite and phosphoric acid-activated carbon for the removal of BOD, COD, and TSS from textile effluents. The activation processes significantly altered the physicochemical properties of both adsorbents. The moisture content of activated carbon decreased from 18% to 3.10%, while ash content was reduced from 15% to 3.05%. The iodine number, indicative of adsorption capacity, increased from 650 mg/g to 810 mg/g. Additionally, the fixed carbon content improved from 55% to 80%. Surface characterization via Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) confirmed substantial structural modifications, which enhanced the adsorption performance of the materials. Application of the combined adsorbent system resulted in substantial pollutant removal efficiencies, with reductions of 70.23% in BOD, 70.11% in COD, and 74.88% in TSS. These findings demonstrate that acid-activated bentonite and phosphoric acid-treated activated carbon represent a promising and efficient adsorptive treatment strategy for the remediation of textile wastewater.